The underpricing of initial public offerings in the Athens stock exchange - Νούνης, Χρήστος Π. (SPOUDAI Journal of Economics and Business, 2006)
This study investigates the price performance of initial public offerings (IPOs) launched on the Athens Stock Exchange (A.S.E.) during the period 1994-2002. Specifically, it examines the differences between the listing price of IPOs and their equilibrium market prices formed at the end of the first day and at the end of some pre-determined days during the first year of stocks' trading. We find that Greek IPOs had on average large positive initial returns as well as positive one-year returns. The finding of positive one-year returns is inconsistent with international evidence. The IPO puzzle on the Greek stock market is also examined according to the new issues listing board classification - Main, Parallel or New Market of the A.S.E. - during the period 1994-2002. JEL Classifications: G24, G32, G14